2015
DOI: 10.1038/hr.2015.16
|View full text |Cite
|
Sign up to set email alerts
|

Combined Aliskiren and L-arginine treatment reverses renovascular hypertension in an animal model

Abstract: Renovascular hypertension is characterized by increased renal sympathetic activity, angiotensin II and by endothelial dysfunction. The purpose of this study was to determine the role of renal sympathetic nerve activity (RSNA) in mediating the anti-hypertensive effects of aliskiren (ALSK) and L-arginine (L-ARG) in a rat renovascular hypertension model. Hypertension was induced by clipping the right renal artery, and the following five groups were divided: SHAM operated; 2-kidney, 1-clip (2K1C); 2K1C plus ALSK; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 40 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…Percutaneous transluminal renal angioplasty (PTRA) has been one of the common treatments for RAS despite recent developments in therapeutics [2, 3]. Using retrospective data, Bonelli et al reported that 60–90% of 320 RAS patients who underwent PTRA exhibited some benefits after PTRA [4].…”
Section: Introductionmentioning
confidence: 99%
“…Percutaneous transluminal renal angioplasty (PTRA) has been one of the common treatments for RAS despite recent developments in therapeutics [2, 3]. Using retrospective data, Bonelli et al reported that 60–90% of 320 RAS patients who underwent PTRA exhibited some benefits after PTRA [4].…”
Section: Introductionmentioning
confidence: 99%
“…11 In contrast to conventional rennin-angiotensin system (RAS) blockers, aliskiren blocks the renin system by directly inhibiting plasma renin activity and prevents the formation of both angiotensin I (Ang I) and angiotensin II (Ang II). 12 Accumulating experimental and clinical evidence support that aliskiren has demonstrated antihypertensive efficacy comparable with or even superior to that of other classes of antihypertensive drugs, including angiotensin converting enzyme inhibitors (ACEIs) and angiotensin AT1-receptor blockers (ARBs). 13,14 Evidence has suggested that aliskiren improves endotheliumdependent vasodilation and NO availability in the peripheral resistance arterioles of hypertensive patients.…”
Section: Introductionmentioning
confidence: 99%
“…Aliskiren, a novel non‐peptide and oral renin inhibitor, has been approved for the treatment of hypertension . In contrast to conventional rennin–angiotensin system (RAS) blockers, aliskiren blocks the renin system by directly inhibiting plasma renin activity and prevents the formation of both angiotensin I (Ang I) and angiotensin II (Ang II) . Accumulating experimental and clinical evidence support that aliskiren has demonstrated antihypertensive efficacy comparable with or even superior to that of other classes of antihypertensive drugs, including angiotensin converting enzyme inhibitors (ACEIs) and angiotensin AT1‐receptor blockers (ARBs) …”
Section: Introductionmentioning
confidence: 99%